2012
DOI: 10.2165/11632860-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Medication Management of Paediatric Obsessive-Compulsive Disorder

Abstract: Paediatric obsessive-compulsive disorder (OCD) is a common, yet under-recognized, neuropsychiatric illness in both clinical and community settings. Symptoms tend to be hidden or misunderstood by affected youth, and parents may inadvertently accommodate OCD, thus worsening its severity. These symptoms may include compulsive reassurance seeking, confessing and 'just right' rituals, in addition to more classic OCD behaviours. Fortunately, numerous psychometric measures are available to assist in clinical assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…An additional consideration is that the degree of symptom-based shame may vary depending on the obsessional content. A number of conceptual and case descriptions suggest that shame is especially likely in response to violent or sexual obsessions (Berle and Phillips, 2006; Cougle et al, 2008; Herbst et al, 2012; Marsanic et al, 2011; Stewart et al, 2012; Torres et al, 2001). The only empirical study of this issue in a clinical sample (Kim et al, 2013) revealed no significant correlations of specific OCD symptoms with shame (partial r s all non-significant and ranging from −.08 to .24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional consideration is that the degree of symptom-based shame may vary depending on the obsessional content. A number of conceptual and case descriptions suggest that shame is especially likely in response to violent or sexual obsessions (Berle and Phillips, 2006; Cougle et al, 2008; Herbst et al, 2012; Marsanic et al, 2011; Stewart et al, 2012; Torres et al, 2001). The only empirical study of this issue in a clinical sample (Kim et al, 2013) revealed no significant correlations of specific OCD symptoms with shame (partial r s all non-significant and ranging from −.08 to .24).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, shame in OCD may be maintained, and even exacerbated, by the treatment avoidance and social withdrawal that shame promotes. Numerous observations in the clinical OCD literature note that shame leads to avoidance of disclosing symptoms to treatment providers or loved ones (Abbey et al, 2007; Bram and Bjorgvinsson, 2004; Canavera et al, 2009; Chavira et al, 2008; Herbst et al, 2012; Kim et al, 2013; Marsanic et al, 2011; Monti et al, 1998; Moritz, 2008; Moritz and Jelinek, 2008; Moritz et al, 2011; Newth and Rachman, 2001; Rothenberg, 1998; Salkovskis, 1990; School, 2005; Simonds and Thorpe, 2003; Stewart et al, 2012; Sulkowski et al, 2011; Vythilingum and Stein, 2005; Williams et al, 1998; Zohar et al, 2007). Moreover, some authors anecdotally observe that such avoidance likely impedes social functioning and support (Abbey et al, 2007; Nymberg and Van Noppen, 1994; Sorensen et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…SLITRK5 knockout mice display a pathologic over-grooming phenotype that is accompanied by disrupted corticostriatal circuit activity. Moreover, pathologic grooming behavior in SLITRK5 knockout mice is normalized by serotonin reuptake inhibitors; the most effective pharmacologic treatments for OCD [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the effi cacy of SSRIs in the treatment of OCD in both adults and children ( 278 ). The clear superiority of this class of medications makes them the fi rst-line treatment for OCD.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%